الهندسة البشرية وعلاقتها بالانهماك الوظيفي لأعضاء هيئة التدريس بجامعات المملكة العربية السعودية - المدرع، سفر بن بخيت المدرع; الرويس، شيخة سلطان (جامعة سوهاج - كلية التربية, 2019)
هدفت الدراسة الحالية إلى معرفة مدى توافر أبعاد الهندسة البشرية، ومدى ممارسة أعضاء هيئة التدريس بجامعات المملكة العربية السعودية للانهماك الوظيفي، وبيان ما إذا كانت هناك علاقة ارتباطية بينهما، وتم استخدام المنهج الوصفي المسحي، بواسطة استبانة للهندسة البشرية، مكونة من عدد (٦٠) عبارة، وأخرى للانهماك الوظيفي، مكونة من عدد (٤٥) عبارة، وكلاهما من إعداد الباحثين، طبقت أدوات الدراسة على عينة بلغ عددها (٢٣٩) عضو هيئة تدريس من أعضاء هيئة التدريس بالجامعات السعودية، تم تعيينهم بالطريقة العشوائية الطبقية، وكان من أهم نتائج الدراسة: أن توفر أبعاد الهندسة البشرية في الجامعات السعودية جاء بتقدير توفر (متوسط) في أبعادها الثلاثة (الإنساني، التنظيمي، والبيئي)، كما أن ممارسة أعضاء هيئة التدريس في الجامعات السعودية لأبعاد الانهماك الوظيفي جاء بتقدير ممارسة (متوسط) في أبعاده الثلاثة (الفكري، السلوكي، والعاطفي)، كما وجدت الدراسة أن هناك علاقة إيجابية بين مدى توافر أبعاد الهندسة البشرية ومدى ممارسة أعضاء هيئة التدريس بالجامعات السعودية للانهماك الوظيفي، وبناء على تلك النتائج أوصت الدراسة بضرورة تطوير بيئات عمل تتوفر فيها معايير أبعاد الهندسة البشرية والتي يؤمل أن تسهم بشكل كبير في تعزيز الانهماك الوظيفي لدى أعضاء هيئة التدريس.
The aim of this research was to determine the degree of availability of the ergonomics’ dimensions and the level of faculty members’ job engagement in the universities of Saudi Arabia, and to identify if there is any relationship between them. The researchers followed the descriptive survey methodology and used a (60)-item questionnaire for ergonomics' dimensions and another (45)-item questionnaire for the job engagement. A random stratified sample consisting of (239) faculty members in Saudi Arabia universities was selected. The main results were: (an average) degree of availability of ergonomics' dimensions in Saudi universities on the three (human, Regulatory and environmental) dimensions; (an average) degree of availability of the dimensions of job engagement in Saudi universities on the three (intellectual, behavioral and emotional) dimensions; and finally, a positive relationship between the degree of availability of ergonomics’ dimensions and the degree of job engagement of the faculty members. Based on these results, the researchers recommend the development of working environments that meet the standards of ergonomics' dimensions in Saudi universities that will, most likely, contribute in the improvement of faculty members’ job engagement.
Keywords: السعودية -- التعليم العالي -- هيئة التدريس -- تنمية الموارد البشرية -- خطط التنمية